Estilos de crianza y desarrollo emocional en los niños de Educación Inicial II de la Unidad Educativa Eugenio Espejo. Período Lectivo 2023-2024 - Paccha Uchuari, Janeth Lourdes (2024)
Parenting styles and emotional development in children of Initial Education II of the Eugenio Espejo Educational Unit, focus on the attitudes, behaviors and practices that parents or carers use to interact with their children and guide their growth, so influencing their emotional, social and academic well-being.The main objective of this research is to analyze how these parenting styles affect the emotional development in children of Initial Education II in the Eugenio Espejo Educational Unit. The methodology used in the study is qualitative, non-experimental and cross-sectional design With a sample of 20 children and two teachers, were obtained the following results: parenting styles that positively influence in the emotional development in children are the democratic, based on establishing clear limits and mutual respect, rising independent and responsible children. Likewise, the style that negatively influences in the emotional development of children is the permissive, characterized by the lack of authority and by the parent’s teaching, which leads to the child not complying with the rules dictated by the teacher. It can be concluded, that these results highlight the importance of considering the influence of breeding styles in the children emotional well-being. Emphasizing the need to promote good parenting practices that promote a healthier emotional, personal, social and academic development. Keywords: Family, Managing feelings, Emotion Management, Family Participation.